Prognostic factors in non-Hodgkin lymphomas - Cecyn, Karin Zattar; Oliveira, José Salvador Rodrigues de; Alves, Antônio Correia; Silva, Maria Regina Regis; Kerbauy, José (São Paulo Medical Journal, 2000)
CONTEXT: In Hodgkin’s disease, each clinical or pathologic stage can be related to the extent of the area involved and predicts the next anatomical region at risk for tumor dissemination. OBJECTIVE: To determine the best prognostic factors that could predict survival in non-Hodgkin lymphoma cases. DESIGN: A retrospective study. LOCATION: Department of Hematology and Transfusion Medicine, Universidade Federal de São Paulo - Escola Paulista de Medicina. PARTICIPANTS: 142 patients with non-Hodgkin lymphoma diagnosed between February 1988 and March 1993. MAIN MEASUREMENTS: Histological subset, Sex, Age, Race, B symptoms, Performance status, Stage, Extranodal disease, Bulk disease, Mediastinal disease, CNS involvement, BM infiltration, Level of DHL, Immunophenotype. RESULTS: In the first study (113 patients), the following variables had a worse influence on survival: yellow race (P<0.1); ECOG II, III e IV (P<0.1) and extranodal disease (P<0.1) for high grade lymphomas; constitutional symptoms (P<0.1), ECOG II, III e IV (P<0.1) and involvement of CNS (P<0.1) for intermediate grade and the subtype lymphoplasmocytoid (P=0.0186) for low grade lymphomas. In the second survey (93 patients), when treatment was included, the variables related to NHL survival were: CNS involvement (P<0.1) for high grade lymphomas, constitutional symptoms (P<0.1), ECOG II, III, IV (P=0.0185) and also CNS involvement (P<0.1) for the intermediate group. There were no variables related to the survival for low-grade lymphomas. CONCLUSIONS: The intermediate grade lymphomas were more compatible with data found in the literature, probably because of the larger number of patients. In this specific case, the treatment did not have an influence on the survival.